Stability Analysis for Steady State Solutions of Huxley Equation - Saad Manaa; Mohammad Sabawi (Al-Rafidain Journal of Computer Sciences and Mathematics)
Stability analysis of steady state solutions of Huxley equation using Fourier mode stability analysis in two cases is investigated. Firstly when the amplitude is constant and secondly when the amplitude is variable and the results were found to be: The solutions and  are  always stable while the solutions  and  are conditionally stable. In the second case, a comparison between the analytical solution and the numerical solution of Galerkin method is done and the results are the same.